DIAGNOSTIC ANALYSIS OF THE UTILIZATION OF WORDWALL MEDIA IN DEVELOPING CRITICAL THINKING ABILITIES IN ELEMENTARY SCHOOL MULTIPLICATION LEARNING - Noer Mahmudiyah; Neni Mariana; Wiryanto (Universitas Majalengka, 2025)
The lack of student participation in multiplication learning in elementary schools is still a challenge for educators. One approach that can be used to increase student engagement and understanding is gamification, which is the integration of game elements in the learning process. This study aims to explore the effectiveness of the use of Wordwall media in multiplication learning through a case study in grade III UPT SD Negeri 30 Gresik. The study highlights how the Multiplication Balloon Burst game can increase student engagement, as well as develop their critical thinking skills in solving math problems. This study uses a qualitative approach with a case study method, where data is collected through observation of classroom activities, interviews with teachers and students, and analysis of student participation during digital game-based learning. The results show that the use of Wordwall games significantly increases student motivation, creates a more interactive learning environment, and improves understanding of multiplication concepts. In addition, the findings indicate that the integration of gamification elements, such as the scoring system and in-game challenges, can encourage students to participate more actively and think critically in solving multiplication problems. This study concludes that the use of digital-based educational games in mathematics learning can be an effective alternative in improving student learning outcomes. Furthermore, the game also facilitates collaborative learning and assists students in developing critical thinking skills. Therefore, educators are advised to consider the application of gamification in their teaching strategies to improve student engagement as well as their learning outcomes in various other mathematical concepts.